Role of Molecular Diagnosis in Imported Cutaneous Leishmaniasis and Its Public Health Significance in India - Rohit Sharma; Deepti Singh; S. Muthukumaravel; S. L. Hoti; Laxmisha Chandrashekar; Manju Rahi (Pathogens)
Cutaneous leishmaniasis (CL) is a significant public health concern that affects many countries. This disease is caused by the protozoan parasite Leishmania spp. and is transmitted through the sandflies from the genus Phlebotomus and Lutzomyia. The clinical manifestations of CL can vary, often leading to challenges in accurate diagnosis and treatment. In 2022, a 51-year-old male patient presented to a tertiary care hospital in Puducherry, India, with progressively worsening facial lesions and granulomatous plaques. The patient had recently returned from Saudi Arabia, where he likely contracted the infection. Before he visited the tertiary care hospital in Puducherry, the patient had been misdiagnosed and treated for conditions such as Erysipelas and Acute Cutaneous Lupus Erythematosus (ACLE), highlighting the diagnostic challenges associated with CL. Skin scrapings from the patient were subjected to real-time PCR, confirming Leishmania spp.’s presence. Cytological examinations revealed the amastigote-like structures within macrophages, thereby establishing the identity of the parasite. For precise species-level identification, PCR-Restriction Fragment Length Polymorphism (PCR-RFLP) and Sanger sequencing of the Internal Transcribed Spacer-1 (ITS-1) region were performed. Molecular techniques confirmed the infection as being caused by Leishmania tropica. Following the accurate diagnosis, the patient was successfully treated with Liposomal Amphotericin B, a treatment known for its efficacy against Leishmania infections. This case underscores the critical importance of considering cutaneous leishmaniasis in the differential diagnosis of travelers returning from endemic areas who present with dermatological manifestations. The initial misdiagnosis and inappropriate treatment highlight the need for heightened clinical awareness and the utilization of advanced diagnostic tools for accurate identification. Effective and timely treatment, as demonstrated in this case, is essential for the management and control of the disease. This report emphasizes the necessity of vigilance among healthcare providers to recognize and appropriately address imported cases of cutaneous leishmaniasis.